Method to Recover from Meniscus Tearing - Li, Yichen (Transactions on Materials, Biotechnology and Life Sciences, 2024)
A torn meniscus, a prevalent knee injury, holds significant importance due to its impact on post-surgery outcomes. Failure to undergo timely and appropriate rehabilitation can result in numerous complications, including muscle atrophy and limited joint mobility. Current research has made strides in assessing the efficacy of various rehabilitation protocols for patients with meniscus tears, aiming to restore strength and functionality to the affected knee. Despite progress, challenges persist, such as determining the optimal timing and intensity of rehabilitation exercises and addressing individual variability in recovery rates. Thus, the crux lies in selecting tailored treatments that address the specific nature and severity of the meniscus injury, aiming to mitigate post-operative complications like muscle atrophy and ensure comprehensive recovery.